ANALISIS USAHA PENGAWETAN TRADISIONAL IKAN ASAP DI DESA LIANG ILIR DAN LIANG ULU KECAMATAN KOTA BANGUN KABUPATEN KUTAI KARTANEGARA - Rahman; Elly Purnamasari; Muhammad Syafril (2339-1324, 2022)
The research objectives were to determine the traditional smoked fish preservation process, to determine the level of income from traditional smoked fish preservation, to determine the feasibility of traditional smoked fish preservation based on the criteria of R/C, Break Event Point (BEP), Payback Period (PP) and Return of Investment (ROI) and know the marketing channels of the traditional smoked fish preservation business in Liang Ilir and Liang Ulu Villages, Kota Bangun District, Kutai Kartanegara Regency. This research was conducted for 12 months from March 2020 to February 2021 in Liang Ilir and Liang Ulu Villages, Kota Bangun District, Kutai Kartanegara Regency. The research method used was a survey, while the sampling of traditional smoked fish preservation was carried out by purposive sampling. The results of research on the traditional preservation process of smoked fish in Liang Ilir and Liang Ulu villages are starting from the process of weeding and washing fish, smoking, packaging, and storing. Traditional smoked fish preservation is feasible. economy with an average feasibility indicator value of R/C value of 1.32, the value of the Break Event Point (BEP) of the selling price of Rp. 147,700, -/kg, total production of 158.61 kg/month and total sales of Rp. 525,781,-/month, the Payback Period (PP) is 1.98 months, and the Return of Investment (ROI) is 55.23% and the smoked fish preservation marketing channels are zero-level channels (producers - consumers) and one-level channels (producers - retailers - consumers). Keywords: Business analysis, Preservation, Marketing Channels